Construction and Evaluation of Composite Scaffold Properties of Cellulose Base Enhanced with Calcium Alginate Containing Propolis for Use in Skin Tissue Engineering - Asri, Maryam; Asefnejad, Azadeh; Naeimi, Mitra (Journal of Asian Scientific Research, 2020)
Ideal wound dressing materials should meet the requirements including maintaining a local moist environment, good surface absorbance for wound exudate, decreasing wound surface necrosis, and avoiding the lack of moisture in the wound. Common treatments for infections caused by skin diseases, resulting in extensive damage and often cause the death of people. In this project, the electrolytic solution of carboxymethylcellulose / calcium alginate / propolis was used to fabricate suitable fiber diameter and uniform distribution. Cellulose is suitable for the grafting of a myriad of chemical groups because of the ample availability of hydroxyl groups, and Propolis was selected in this research due to its excellent properties, such as accelerating wound healing and cell growth and antibacterial growth. The optimum electrospinning conditions were achieved at a voltage of 20 kV, with a spacing of 20 cm from the syringe to the collecting plate and a rate of 15 ml / h. Then, to evaluate the properties of the scaffold. Scanning electron microscopy (SEM), infrared Fourier transform (FTIR), mean of weight loss were performed. Finally, for testing the cellular survival of the samples MTT test was performed and a mechanical test was performed on the specimens. The scaffold degradation rate was linear and resulted in its complete destruction in 21 days. Cytotoxicity testing of scaffolds yielded acceptable results. A suitable structure for porosity and permeability was obtained in calcium carboxymethylcellulose/calcium alginate/propolis scaffold and this scaffold is a good candidate for application in skin tissue engineering.